ANALISIS BIAYA-VOLUME-LABA SEBAGAI ALAT BANTU DALAM PERENCANAAN LABA - Heru Harmadi Sudibyo (Jurnal Ilmu dan Budaya, 2019)
This study aims to determine the factors that affect earnings. And the implementation of cost-volume-profit analysis in conducting this research. This is based on the cost-volume-profit concept that explains the relationship between cost, sales volume, and profit. Before applying a cost-volume-profit analysis, the researcher classifies the first production cost and nonproduction costs. Then the researcher measures the development pattern of cost data, selling price, and sales quantity by using time series analysis where the equation obtained can be used to forecast the cost, selling price, and the quantity of sales. Then the researcher uses the basics of cost-volumeprofit analysis consisting of several element of analysis that is base of costvolume-profit analysis consist of contribution margin analysis, break even analysis, margin analysis. The results show that the composition of sales revenue is not able to cover fixed costs because in a state of loss. Breakeven point analysis shows that sales record is still below the minimum limit so that it can not reach Break Even Points. In addition, there is utilization of costvolume-profit analysis for profit planning which consists of target profit analysis and sensitivity analysis. This analysis is used to determine the level of sales that must be achieved to achieve the target profit and how fixed costs, variable costs, selling prices, and sales quantity can affect  achievement of profit